2014
DOI: 10.2174/1568026614666140901130843
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Inhibition of G-Protein Coupled Receptor Oligomerization: Strategies and Challenges for Drug Development

Abstract: G-protein coupled receptors (GPCRs) mediate a large number of biological pathways and are major therapeutic targets. One of the most exiting phenomena of GPCRs is their ability to interact with other GPCRs. GPCRGPCR interactions, also known as GPCR oligomerization, may create various functional entities such as homo- and heterodimers and also form complex multimeric GPCR clusters. In many biological systems, GPCR-GPCR interactions are crucial for signal regulation. The interaction with other receptors results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Kniazeff et al (2011) reviewed that dimer formation is a prerequisite for canonical receptor function in class C GPCRs, and Xue et al (2015) demonstrated that the mGluR2 dimer interface switches from TM4-TM5 in the inactive state to TM6-TM6 interactions in the active conformation, revealing a key step in class C GPCR activation. In the large subfamily A of GPCRs, although several receptors are able to operate as monomers (Chabre and le Maire, 2005; Ernst et al, 2007; Hanson et al, 2007; Whorton et al, 2007, 2008; Kuszak et al, 2009; Arcemisbéhère et al, 2010; Bayburt et al, 2011), experimental data have shown that most receptors could be expressed as a mixture of monomers and homodimers/oligomers (Teichmann et al, 2014; Vischer et al, 2015; Franco et al, 2016; Nemoto et al, 2016), and that oligomerization is necessary for the maturation of the receptor, its inclusion in the membrane and its function (Angers et al, 2000, 2002; Fotiadis et al, 2003; Herrick-Davis et al, 2006; Lopez-Gimenez et al, 2007; Han et al, 2009; Wade et al, 2011; Ng et al, 2013; Hurevich et al, 2014; Liste et al, 2015; Gahbauer and Böckmann, 2016; Lao et al, 2017; Jin et al, 2018). Fung et al (2009) reported receptor oligomers, mostly with tetrameric structure, of β2-adrenergic receptors after reconstitution into phospholipid vesicles.…”
Section: The Discovery Of the Cannabinoid Receptorsmentioning
confidence: 99%
“…Kniazeff et al (2011) reviewed that dimer formation is a prerequisite for canonical receptor function in class C GPCRs, and Xue et al (2015) demonstrated that the mGluR2 dimer interface switches from TM4-TM5 in the inactive state to TM6-TM6 interactions in the active conformation, revealing a key step in class C GPCR activation. In the large subfamily A of GPCRs, although several receptors are able to operate as monomers (Chabre and le Maire, 2005; Ernst et al, 2007; Hanson et al, 2007; Whorton et al, 2007, 2008; Kuszak et al, 2009; Arcemisbéhère et al, 2010; Bayburt et al, 2011), experimental data have shown that most receptors could be expressed as a mixture of monomers and homodimers/oligomers (Teichmann et al, 2014; Vischer et al, 2015; Franco et al, 2016; Nemoto et al, 2016), and that oligomerization is necessary for the maturation of the receptor, its inclusion in the membrane and its function (Angers et al, 2000, 2002; Fotiadis et al, 2003; Herrick-Davis et al, 2006; Lopez-Gimenez et al, 2007; Han et al, 2009; Wade et al, 2011; Ng et al, 2013; Hurevich et al, 2014; Liste et al, 2015; Gahbauer and Böckmann, 2016; Lao et al, 2017; Jin et al, 2018). Fung et al (2009) reported receptor oligomers, mostly with tetrameric structure, of β2-adrenergic receptors after reconstitution into phospholipid vesicles.…”
Section: The Discovery Of the Cannabinoid Receptorsmentioning
confidence: 99%
“…The mGlu 1 has been considered to be an important target of the known structure of class C GPCRs for structure-based drug design 19 . Due to the specific allosteric sites in the 7TM domain of mGlu 1 , negative allosteric modulators (NAM) can be designed based on the crystal structure or known NAM 3 20 21 . The cholesterols are considered as the lipid rafts to pack the lipids and membrane proteins tightly 22 .…”
mentioning
confidence: 99%